Experiences gained and major challenges for the remediation of Wismut’s Culmitzsch tailings pond - Barnekow, U; Müller, J; Metschies, T; Paul, M (Mine Closure 2012: Proceedings of the Seventh International Conference on Mine Closure, 2012)
From 1960 to 1990 the former Soviet-German Wismut company milled uranium ore and processed a total of about 110,000 t of uranium at the Seelingstaedt mill in Thuringia, Germany. As part of its mine closure program the state-owned Wismut GmbH is remediating the Culmitzsch Uranium tailings pond covering 2.4 km² (vol. 85 M m³). To date, the Culmitzsch tailings pond has been partly interim covered and re-contoured. Final covering, landscaping and vegetation including hydraulics constructions are foreseen to be completed by 2022. The paper presents experiences gained and conclusions from the management of contaminated waters within the overall water management of the site. In addition the paper presents on-site-monitoring results of ongoing tailings consolidation influencing the overall water management of the site. Experiences from water management and the major challenges for granting the future remediation progress for the entire site are discussed with regard to the technical conditions and legal restrictions for water release to the receiving streams and concepts for surface cover design. Finally the paper provides an outlook to the long term after remediation.